Um estudo sobre as relações de gênero no World of Warcraft - Oliveira, Linderson Christian Sales de (2021)
The increasing popularity of online games and the video game industry has enabled more and more new users or players to enter this world of digital games. These games, also understood as a form of computational art, have provided, from graphic, sound, textual and other elements, a new possibility of insertion and interaction of human beings in virtual worlds. Among the various types of existing games, the MMORPG stands out as a field of possibilities for communication, representation and gender interactions in the technological era, mainly because it uses the internet as an essential support point. Understanding the interaction dynamics within MMORPG games is seeking to understand the new forms of human relationships that are being built in these virtual spaces. Given the above, this study seeks to investigate the relationships and interactions between players of different genders in the Massive Multiplayer Online Role-Playing Game, World of Warcraft. In order to understand the aforementioned aspects, an exploratory field research of a qualitative nature was carried out, using an online questionnaire formulated by the researcher himself based on the study objectives as an instrument for data collection, which was applied to thirty eight participants. The data obtained from this questionnaire were analyzed using the IRAMUTEQ qualitative data analysis support software. The results demonstrate that digital games have multiple potentials, which can have a positive or negative character for the players inserted in this space. We observed that games can be a place for social interaction, leisure, entertainment and learning, as well as it is also possible to find behaviors of violence associated with machismo and misogyny. Therefore, the research revealed that the social and gender dynamics in the gaming environment are complex and ambivalent. Finally, it is expected that the results of this study can contribute to a greater understanding of the interactions between different genders that occur in the space of online digital games.